2007
DOI: 10.1016/j.jet.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic inefficiency in an overlapping generations economy with production

Abstract: Reichlin (JET, 1986) has shown in an OLG model with productive capital that whenever the steady state is locally indeterminate and undergoes a Hopf bifurcation, it is Pareto-optimal. While these results were established under the assumption of Leontief technology, the author has partially extended them to show that the Hopf bifurcation is robust with respect to the introduction of capitallabor substitution. In this note, we prove that the Pareto-optimality of the steady state does not extend to technologies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In contrast, when local indeterminacy occurs under dynamic inefficiency, stabilization policies targeting the steady state leave room for welfare losses. Although Reichlin (1986) has shown that locally indeterminate dynamically efficient equilibria can occur in an aggregate model with a Leontief technology, Cazzavillan and Pintus (2007) have recently proved that this result is not robust to the introduction of any positive capital-labor substitution.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when local indeterminacy occurs under dynamic inefficiency, stabilization policies targeting the steady state leave room for welfare losses. Although Reichlin (1986) has shown that locally indeterminate dynamically efficient equilibria can occur in an aggregate model with a Leontief technology, Cazzavillan and Pintus (2007) have recently proved that this result is not robust to the introduction of any positive capital-labor substitution.…”
Section: Introductionmentioning
confidence: 99%
“…The OLG model, which has become an engine for economic analysis, can exhibit complicated dynamic behavior involving oscillations, chaos and bifurcations (see [5], [18], [24]). It is demonstrated that there are many causes of bifurcation in the OLG system, such as pollution perception ( [22]), different utility functions ( [15]), markup variability ( [10]), productive externalities ( [4]), exponentially fading memory ( [2]) and increasing returns to scale ( [1]).…”
Section: Introductionmentioning
confidence: 99%